Differentiated Digital Teaching Models using ICTs in Greek Context. Good Practices: “Caretta-Carreta” - Paraskevi, Lykou; Chaidi, Irene; Stathopoulou, Agathi; Karabatzaki, Zoe (Eximia, 2022)
Today’s pedagogy supports the inclusion of people with special needs in the general classroom. An Open School, A school for all. The new Technologies are a tool that helps in this direction by turning standard teaching into teaching for everyone. Uniform teaching that adapts to the peculiarities, abilities, interests, and experiences of each student. It helps create and implement differentiated instruction, giving all students the ability to approach knowledge at their own pace and time. In this work, a scenario of differentiated teaching in an environmental project is presented.